Cranberry Juice Capsules and Urinary Tract Infection After Surgery: Results of a Randomized Trial. Issue 12 (December 2015) - Foxman, Betsy; Cronenwett, Anna E. W.; Spino, Cathie; Berger, Mitchell B.; Morgan, Daniel M.
Abstract : ABSTRACT: Most urinary tract infections (UTIs) acquired in hospitals are attributed to the use of a urinary catheter. The risk of UTIs remains high after removal of the catheter; postoperative patients are especially vulnerable. The 6-week cumulative incidence of a symptomatic UTI in women after catheter removal is 10% to 64%, compared with 3% to 4% per year in the general population. Antibiotics administered to postoperative patients at the time of catheter removal reduce UTI incidence by approximately 50%, but the risk of infection remains significant postoperatively (4.7% within 4 weeks) and antibiotic resistance is high. Cranberry juice extracted from the American cranberry ( Vaccinium macrocarpon ) has been widely used to prevent UTIs. A 2012 systematic review and meta-analysis reported an overall protective effect of cranberry on UTI. However, there was considerable heterogeneity in results across trials; methodological problems included variation in dose, sample size, and choice of study population. None of the trials addressed effectiveness of cranberry in reducing the risk of UTIs after catheterization. The aim of this randomized, double-blind, placebo-controlled trial was to determine the therapeutic efficacy of cranberry juice capsules in preventing UTIs after catheter removal in women who had undergone elective gynecological surgery. The study was conducted at a single hospital between August 2011 and January 2013. Eligible participants were nonpregnant women aged 18 years or older whose surgery did not involve a fistula repair or a vaginal mesh removal. A total of 359 women presenting for elective gynecological surgery were screened for eligibility. Of these, 160 met the inclusion criteria and were randomized to receive either 2 cranberry capsules 2 times a day (equivalent to twice daily 8 oz servings of cranberry juice) for 6 weeks after surgery or matching placebo. The primary study outcome measure was the proportion of women who experienced clinically diagnosed and treated UTI with or without positive urine culture. Treatment differences between the 2 groups were assessed using Kaplan-Meier plots and log-rank tests. The incidence of UTI was significantly lower in the cranberry group compared with the placebo group (15 [19%] of 80 vs 30 [38%] of 80; the odds ratio was 0.38, with a 95% confidence interval of 0.19 to 0.79; P = 0.008). The protective effects of cranberry treatment persisted after adjusting for known confounders, which included frequency of postoperative self-catheterization and having an indwelling Foley catheter after discharge from the hospital (odds ratio, 0.42; 95% confidence interval, 0.18–0.94; P = 0.037). No significant differences between groups were found in the incidence of adverse events. The most commonly reported event in both groups was gastrointestinal upset (56% vs 61% for cranberry vs placebo, P = not significant). This is the first double-blind, placebo-controlled randomized clinical trial demonstrating a significant preventive effect of cranberry juice capsules on UTI after catheter removal in women who had undergone elective benign gynecological surgery.